Participative Management and Socio-Environmental Sustainability: a Study of Public Schools of Sobral, CE, Brazil - Brito, Renato de Oliveira; Luiz Síveres; Célio da Cunha (European Journal of Multidisciplinary Studies, 2018)
In this study we analyze indicators of the influence of participative management on the development of school projects envisaged by the Direct Funding in the School Program – Sustainable Schools (Programa Dinheiro Direto na Escola – PDDE – Escolas Sustentáveis), which aimed to promote socio-environmental education. Data were generated through semi-structured interviews with principals, teachers, coordinators, and students in four schools included in the program. Based on a group of 15 participants, results confirm the premise that participative management, with the addition of institutional financial support for school projects, enriched both the school and social community regarding issues of conservation and preservation of the environment for the purpose of enabling better quality of life for present and future generations. Broad participation and discussion were the foundation for identification of the meanings/sense (import) the participants attach to their actions and achievements in the schools. This culminated in creating what we here designate as indicators of socio-environmental sustainability in schools with participative management.